Profit Loss Sharing Problemsin the Banking Industry in Indonesia - Fahamsyah, Mohammad Hatta; Zaki, Irham; Laila, Nisful; Shahzad Shabbir, Malik (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: This systematic literature review provides an overview of profit and loss sharing (PLS) in the Indonesian Islamic banking industry. The study aims to identify the development of Islamic banking, as well as the challenge and opportunities of PLS products and services in Islamic banking Methods: This research utilizes a systematic literature review methodology employing a qualitative approach, using databases, including SINTA and Google Scholar, to identify relevant articles and studies. A total of 609 journal articles were initially identified. Results: The findings of the study indicate that the Indonesian Islamic banking industry has experienced significant growth in recent years. However, the market share of Islamic banks in Indonesia is still relatively small compared to conventional banks. The development of PLS products and services has been a key factor in this growth Conclusion and suggestion: The study concludes that PLS is an important feature of Islamic banking and has numerous opportunities to be targeted. Meanwhile, PLS Scheme has challenges and negative potential for Indonesian Islamic banking. Hence, because of this negative potential, high risk, and competitiveness issue. However, Further investigation is warranted to delve into empirical research studies that examine the potential of profit and loss sharing as well as revenue sharing mechanisms within Islamic banking, along with their implications for the Indonesian economy.